Exploring the relationship between frailty, physical activity, and swallowing - Mappanasingam, Anittha (My University, 2025)
Dysphagia awareness remains low among the general population, contributing to the number of individuals living with undetected dysphagia. Anecdotal reports emphasize the lack of funding and long waitlists for speech-language pathology services, making it difficult for individuals to receive a dysphagia diagnosis and timely rehabilitation. Additionally, there are limited and inconsistent results regarding the efficacy of current swallowing rehabilitation techniques, highlighting the need for accessible management dysphagia strategies. The goal of this thesis is to explore ways to identify dysphagia early on and expand current swallowing management strategies to increase accessibility. The primary aim of the first study is to confirm the relationship between frailty and dysphagia using objective, gold-standard measures in community-dwelling older adults (60 to 89 years of age) living in Ontario and Halifax. The secondary aim is to determine if functional capacity and physical activity modify or change this relationship. This cross-sectional study performed a multi-linear or logistic regression analysis between physical frailty via the Fried Physical Frailty Phenotype (FPFP) and dysphagia via the Dynamic Imaging Grade of Swallowing Toxicity (DIGEST) scores based on videofluroscopic swallowing studies, self-reported Eating Assessment Tool (EAT) - 10 scores, and proxy measures of swallowing such as, anterior and posterior maximum isometric tongue pressure; regular effort saliva swallow pressure; voluntary peak cough flow (Aim 1). Sub-group analysis of functional capacity via Short Physical Performance Battery test and physical activity via Physical Activity Scale for the Elderly was performed to determine the role of functional capacity and physical activity on frailty and dysphagia (Aim 2). Normative mean values based on existing research were used as cut-offs for functional capacity and physical activity. This study consisted of 114 participants with a mean age  standard deviation (SD) of 72  8 years. For aim 1, frailty was only significantly associated with dysphagia when assessed using EAT-10 scores. Frailty was not significantly associated with DIGEST scores, anterior or posterior maximum isometric tongue pressure, maximum regular effort saliva swallow, and voluntary peak cough flow. For aim 2, frailty was significantly associated with EAT-10 scores at low levels of functional capacity, high levels of functional capacity, and low levels of physical activity. These findings suggest that frailty may be associated with areas of dysphagia that cannot be identified using videofluroscopies but can be identified using self-reported measures, such as increased effort or fatigue during swallowing, and how physical activity may serve as a protective factor to prevent frail older adults from developing dysphagia. The second study was a scoping review that explored the impact of physical exercise on structures and functions involved in swallowing in mature animal models or adult humans. Seven databases were searched for relevant studies on May 26, 2025. Studies were only included if the whole-body intervention included details such as dose and frequency and if effects of whole-body exercise were differentiable from other exercises in combined interventions. The search resulted in four studies (two animal studies, two human studies). The interventions included treadmill running, stationary cycling and cardiovascular conditioning combined with dual task strengthening. Swallowing was assessed using myosin heavy chain isoforms, tongue contractile properties, bite force, EAT-10 questionnaire, anterior and posterior maximum isometric tongue pressure, and voluntary peak cough flow. Physical exercise was found to influence swallowing in animal models but not in humans. Descriptive analysis of one of the human studies found self-reported swallowing function to improve in majority of individuals after physical exercise. A limited number of studies were identified in this review, but findings still suggest that physical exercise may impact swallowing and future research should continue to explore this topic. Together these studies suggest that clinicians can use frailty to identify those who are at-risk of dysphagia and highlight the importance of future work to investigate publicly available and accessible strategies to manage dysphagia.
Keywords: dysphagia; frailty; older adults; physical activity; exercise; swallowing